Penentuan Kelembaban Tanah Optimum Untuk Budidaya Padi Sawah SRI (System Of Rice Intensification) Menggunakan Algoritma Genetika - Chusnul Arif; Budi Indra Setiawan; Masaru Mizoguchi (Balai Teknik Irigasi, 2014)
In this study, an optimal soil moisture level that maximizes both yield and water productivity of system of rice intensification (SRI) paddy field was simulated by genetic algorithms (GA) model. The GA model was performed to find an optimal combination of soil moisture levels according to the empirical data during three cropping seasons at Nusantara Organic SRI Center (NOSC), Nagrak Sukabumi, West Java. Here, we classified soil moisture level into three levels i.e. wet (W), medium (M) or dry (D) based on the soil water retention curve. As the results, the optimal soil moisture was a combination of wet, wet, medium, and dry levels of soil moisture for initial, crop development, mid-season and late season growth stages, respectively. The wet level in the initial and crop development growth stages should be achieved providing enough water for the plant to develop root, stem and tiller, and then the field can be drained into the medium level with the irrigation threshold of field capacity to avoid spikelet sterility in the mid-season stage, and finally, let the field in the dry level to save more water in the late season stage when plant water requirement is minimum. By this scenario, it was simulated that the yield can be increased up to 4.40% and water productivity up to 8.40% with saving water up to 12.28% compared to the empirical data.